"I lied a little bit." A qualitative study exploring the perspectives of elite Australian athletes on self-reported data. (March 2023) - Coventry, Molly; Timler, Amanda; Mosler, Andrea B.; Russell, Kylie; Travers, Mervyn; Mitchell OAM, Lauren; Murphy, Myles C.
Abstract: Objectives: Explore the perceptions and experiences of elite Australian athletes' engagement with reporting data in surveillance systems. Design: Qualitative Descriptive. Setting: Semi-structured interviews conducted using Zoom. Participants: We recruited 13 elite Australian athletes competing at a national or international level for semi-structured interviews. Main outcome measures: Audio recordings were transcribed using DeScript, checked for errors and imported into QSR NVIVO. Thematic analysis using QSR NVIVO was used to determine key themes from transcripts. Results: Thematic analysis uncovered four key themes: 'the paradox of reporting', 'data for data's sake', 'eyes on reporting' and 'athlete friendly reporting'. Conclusion: Athletes perceived reporting as a burden and the athlete management system presented numerous technological difficulties which led to athletes to backfill data entries and compromise data accuracy. Athletes had little knowledge on how their data was used and managed and often received minimal feedback from staff accessing the data. Athletes were unaware of who has access to their data, which is of concern as sensitive information may be collected and athletes may be underage. As a result, many athletes chose to report dishonest data to avoid their performance being questioned. Highlights: Athletes perceived self-reporting into surveillance systems as a substantial burden. Athletes reported a lack of transparency on who had access to their data. Athletes reported being dishonest with self-reported data.